Usefulness of Carcinoembryonic Antigen for Monitoring Tumor Progression during Palliative Chemotherapy in Metastatic Colorectal Cancer - Kim, Gangmi (Yonsei University College of Medicine, 2013)
PURPOSE: To evaluate the efficacy of carcinoembryonic antigen (CEA) measurement for monitoring tumor progression during palliative chemotherapy in metastatic colorectal cancer. MATERIALS AND METHODS: Forty-eight patients with initially unresectable metastatic colorectal cancer (n=26, 54.2%) or recurrent unresectable metastatic colorectal cancer (n=22, 45.8%) received FOLFOX-4 chemotherapy for palliation. Serum CEA levels and carbohydrate antigen 19-9 levels were measured and computed tomography (CT) studies were performed prior to chemotherapy and after 3 cycles of chemotherapy. From the CT images, tumor responses were evaluated according to the Response Evaluation Criteria in Solid Tumors criteria and categorized as complete response, partial response, stable disease, and progressive disease. The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of tumor marker assessments for determining tumor response were calculated. RESULTS: The sensitivity, specificity and diagnostic accuracy of CEA assessment for prediction of disease progression were 50%, 77% and 69%, respectively. When the patients were dichotomized according to baseline CEA level, the initially elevated CEA group showed higher sensitivity and higher diagnostic accuracy compared to the initially normal CEA group (sensitivity=67% vs. 20%; diagnostic accuracy=71% vs. 62%). CONCLUSION: CEA assessment could be useful for monitoring tumor progression during palliative chemotherapy in only patients with initially elevated CEA level.